Effects of Exogenous Tryptophan in Alleviating Transport Stress in Pearl Gentian Grouper (Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂) - Jie Cao; Dan Fang; Weiqiang Qiu; Jing Xie (Animals)
Live fish transportation plays a crucial role in the commercial fish trade. Consequently, mitigating stress during transportation is essential for enhancing the survival rate of fish and reducing potential financial losses. In this study, the effectiveness was evaluated of exogenous tryptophan in reducing transport stress in hybrid grouper, Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂. Firstly, the groupers were divided into the following five experimental groups: 40 mg/L MS-222 group, 30 mg/L tryptophan, 50 mg/L tryptophan, 70 mg/L tryptophan, and the control group without additives. Followed by transportation simulation, the fish samples were collected before and after transportation for the determination of antioxidant enzyme activities, apoptosis gene, and inflammatory gene expressions. The results indicated that the superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) activities and malondialdehyde (MDA) levels in all groups were significantly increased, while they were lower in the 50 mg/L Trp treated group compared to the control group (p < 0.05). Compared with the control group in the 50 mg/L Trp, 70 mg/L Trp, and 40 mg/L MS-222-treated groups, serum cortisol and blood glucose levels were significantly increased (p < 0.05), and anti-inflammatory factor (IL-10) gene expression was upregulated and pro-inflammatory factor (IL-1β) gene expression was decreased (p < 0.05). In addition, it was found that the 30 mg/L Trp, 50 mg/L Trp, and 40 mg/L MS-222 treatment groups had less green fluorescence than the control group by measuring the mitochondrial membrane potential, and 50 mg/L Trp and MS-222 showed more red fluorescence in fluorescence images than the other samples at the same sampling time. Therefore, in this study, it was demonstrated that the tryptophan could be used as a new anti-stress agent for hybrid groupers during transport, and additional research is required to identify the specific conditions that yield the best outcomes.